Outlier Detection Method in Linear Regression Based on Sum of Arithmetic Progression - Becker, T.; Effenberger, M.; Hussein, M. A.; Adikaram, K. K. L. B. (TheScientificWorld, 2014)
We introduce a new nonparametric outlier detection method for linear series, which requires no missing or removed data imputation. For an arithmetic progression (a series without outliers) with n elements, the ratio ( R ) of the sum of the minimum and the maximum elements and the sum of all elements is always 2 / n : ( 0,1 ] . R ≠ 2 / n always implies the existence of outliers. Usually, R < 2 / n implies that the minimum is an outlier, and R > 2 / n implies that the maximum is an outlier. Based upon this, we derived a new method for identifying significant and nonsignificant outliers, separately. Two different techniques were used to manage missing data and removed outliers: (1) recalculate the terms after (or before) the removed or missing element while maintaining the initial angle in relation to a certain point or (2) transform data into a constant value, which is not affected by missing or removed elements. With a reference element, which was not an outlier, the method detected all outliers from data sets with 6 to 1000 elements containing 50% outliers which deviated by a factor of ± 1.0 e - 2 to ± 1.0 e + 2 from the correct value.